Non-rodent animal models of osteosarcoma: A review. (2021) - Jarvis, Sommer; Koumadoraki, Evgenia; Madouros, Nikolaos; Sharif, Shayka; Saleem, Amber; Khan, Safeera
Highlights: An ideal animal model of osteosarcoma has yet to be unanimously identified. Non-rodent animal models such as the chick chorioallantoic membrane (CAM) model, pigs and canines have advantages where rodent models are lacking. Non-rodent models shed light on osteosarcoma disease biology as well as provide a basis for future therapeutics. Abstract: Osteosarcoma is extremely malignant, and the most common cancer that affects bone. Current treatments involve surgical resection of the affected area and multi-agent chemotherapy, though survival rate is generally poor for those affected by metastases. As treatment for osteosarcoma has remained unchanged for the past few decades, there is a need for further advancements in the understanding of osteosarcoma biology and therapeutics. Thus, reliable animal models that can accurately recapitulate the disease are required. Though rodents represent the most popular animal model of osteosarcoma, they may not model the disease best. This review analyzes emerging alternative non-rodent animal models of osteosarcoma, such as the chick chorioallantoic membrane (CAM) assay, pigs, and canines. Each of these alternatives offer advantages over classic rodent models for pre-clinical research. Research of these cross-species platforms imparts knowledge of metastases biology and potential new treatments for osteosarcoma.